Exploring the Motivations and Challenges of Teachers Leaving DepEd for Overseas Opportunities - Don T Cahilog; Jelyn S Sarong; Felix E Arcilla, Jr (Randwick International of Education and Linguistics Science Journal, 2023)
This study delves into educators' motivations and challenges leaving the Department of Education (DepEd) for overseas opportunities. The researchers used descriptive qualitative in conducting the study. Based on the findings, it emerges that both emotional and practical considerations influence teachers' decisions to migrate. Foremost among the concerns is the desire for financial stability, contrasted by their deep emotional connection to students and the local education system. Other significant challenges include the need for comprehensive health and well-being provisions, operational efficiency, professional development, and an inclusive work environment. The study underscores the pressing need for reforms within DepEd, emphasizing competitive compensation, streamlined operations, continuous professional growth, and robust health provisions. It was recommended that the Department of Education (DepEd) must prioritize educators' financial and holistic well-being through competitive salaries and regular professional development opportunities. Streamlined administrative processes, proper resource allocation, and integration of global educational insights will foster a more efficient and appealing environment for educators.